Increased antidepressant use during the COVID-19 pandemic: Findings from the Friuli Venezia Giulia region, Italy, 2015–2020. (September 2022) - Pazzagli, Laura; Reutfors, Johan; Lucian, Ejlli; Zerial, Giovanna; Perulli, Alfredo; Castelpietra, Giulio
Highlights: The observed amount of antidepressant (AD) prescriptions in 2020 measured in number of defined daily doses (DDDs) was higher than predicted, particularly in men, in adults and among the classes of selective serotonin reuptake inhibitors and other ADs. The greatest increase of AD use was observed in young people, and in the first four and last two months of 2020, prior and during the first and second stricter Italian lockdowns. The increase in AD prescriptions may indirectly indicate a rise of mental problems and sleeping disorders in the general population, related to the COVID-19 consequences. The increase of AD use might be also related to a hoarding of prescriptions prior to lockdown restrictions. Abstract: Background: Few studies investigated the impact of the pandemic on antidepressant (AD) use. Methods: The Social and Health Information System of Friuli Venezia Giulia region, Italy, provided data on AD use. Sex, age, AD class and month used the amount of AD prescriptions, measured by defined daily doses (DDD) per 1000 inhabitants per day, to compare AD use in 2020 with the period 2015–2019. A linear trend model predicted AD use for 2020, based on years 2015–2019. Results: AD use was on average 20% higher in each month of 2020 when compared with the same month for the period 2015–2019, with an increase of more than 30% in the first four and in the last two months of 2020. The observed AD use in 2020 was higher than predicted, particularly in men, and in the 30–59 years age group. Limitations: Descriptive study of AD use without analysis of data at the individual level. No information on psychiatric diagnoses of AD users. Conclusion: AD use was higher in the first year of the COVID-19 pandemic. Further research is warranted to understand if this may be related to a rise in mental disorders in the general population during the COVID-19 pandemic.